COMPARATIVE ANALYSIS OF MORPHOMETRIC FEATURES OF PETROLEUCISCUS SQUALIUSCULUS (KESSLER, 1872) FROM THE INLAND WATERS OF THE FERGANA REGION (Scientific journal of the Fergana State University, 2024)
Petroleuciscus squaliusculus (Kessler, 1872) is an endemic species of the Aral Sea basin. In our research, it was recorded from the reservoirs of the Fergana Valley. In this article, a comparative analysis of the morphometric parameters of Petroleuciscus squaliusculus distributed in the river Altiariksoy and ditches Koshtepa through the Fergana Region is given, it has been found that there are differences in 7 main morphometric characteristics of this species.